Patients with right bundle branch block and concomitant delayed left ventricular activation respond to cardiac resynchronization therapy. Issue 11 (25th December 2017) - Pastore, Gianni; Morani, Giovanni; Maines, Massimiliano; Marcantoni, Lina; Bolzan, Bruna; Zanon, Francesco; Noventa, Franco; Corbucci, Giorgio; Baracca, Enrico; Picariello, Claudio; Lanza, Daniela; Zuin, Marco; et al.
Abstract: Aims: Right bundle branch block (RBBB) typically presents with only delayed right ventricular activation. However, some patients with RBBB develop concomitant delayed left ventricular (LV) activation. Such patients may show a specific electrocardiographic (ECG) pattern resembling RBBB in the precordial leads in association with an insignificant S-wave in lateral limb leads (atypical RBBB). We therefore postulated that the ECG pattern of atypical RBBB might be able to identify a subgroup of patients likely to respond to cardiac resynchronization therapy (CRT). The purpose of this study was to assess the impact of RBBB ECG morphology on CRT response in patients with heart failure (HF). Methods and results: We evaluated the echocardiographic clinical response of 66 patients with RBBB treated with CRT and followed up for almost 2 years. The patients were divided electrocardiographically into 2 groups: 31 with typical RBBB and 35 with atypical RBBB. Responders were classified in terms of reduction in LV end-systolic volume index (ESVi) ≥ 15% or reduction in the New York Heart Association (NYHA) Class ≥ 1 or Packer score variation (NYHA response with no HF-related hospitalization events or death). The atypical RBBB group presented a longer LV activation time compared with the typical RBBB group (111.9 ± 17.6 vs. 73.2 ± 15.4 ms; P < 0.001). In the atypical and typical RBBB groups, respectively, 71.4% and 19.4% of patients were ESVi responders ( P = 0.001) 74.3% and 32.3% were NYHA responders ( P = 0.002); similarly, 71.4% and 29.0% of patients exhibited a 2-year Packer score of 0 ( P = 0.002). Conclusion: Patients with atypical RBBB, which is a pattern highly suggestive of concomitant delayed LV conduction, may show a satisfactory response to CRT.